If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9T + 9T = 0 Combine like terms: 9T + 9T = 18T 18T = 0 Solving 18T = 0 Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Divide each side by '18'. T = 0 Simplifying T = 0
| 8x+21=5x+90 | | -15=5-q | | 1+x=-4 | | 7(3x-1)=3(2x+5) | | 4-5x=x-3 | | 7.65x+61.2=122.4 | | 0.15d+0.07(1000-d)=130 | | -2+2k+3=-3 | | 4x+28=2x | | 8-3x+7x=15-3x | | 0.125y+0.1(800-y)=85 | | X+1+3=4 | | 2.7(-16)+2.2=2.4(-16)-2.6 | | 3(1)+6= | | 0.05+0.09(3x)=32 | | 6.5y-3=5.5y+1 | | x+(.05x)=49.77 | | -v-2v=-9 | | 6.5y-3=5.5+1 | | 4(g+2)+3=19 | | 42x-7=9-4 | | 4(x+2)=21(x-3) | | 3-v=1 | | 1-3n-2n=-4 | | 1-v-3=0 | | 2.7x+2.2=2.4x-2.6 | | 1-v-3=I | | (3+v)(4v+1)=0 | | 10x+3=3+12x | | 20-6x=34 | | 1-z=7.2 | | 9x^2+11x+9=0 |